Combined Seismic and Geodetic Analysis Before, During, and After the 2018 Mount Etna Eruption. (18th September 2020) - Mattia, M.; Bruno, V.; Montgomery‐Brown, E.; Patanè, D.; Barberi, G.; Coltelli, M.
Abstract: In December 2018, Etna volcano experienced one of the largest episodes of unrest since the installation of geophysical monitoring networks in 1970. The unrest culminated in a short eruption with a small volume of lava erupted, a significant seismic crisis and deformation of the entire volcanic edifice of magnitude never recorded before at Mount Etna. Here we describe the evolution of the 2018 eruptive cycle from the analysis of seismic and geodetic data collected in the months preceding, during, and following the intrusion. We model the space‐time evolution of high‐rate deformation data starting from the active source previously identified from deformation data and the propagation of seismicity in a 3‐D velocity model. The intrusion model suggests emplacement of two dikes: a smaller dike located beneath the eruptive fissure and a second, deeper dike between 1 and 5 km below sea level that opened ~2 m. The rise and eruption of magma from the shallower dike did not interrupt the pressurization of a long‐lasting deeper reservoir (~6 km) that induced continuous inflation and intense deformation of the eastern flank. Shortly after the intrusion, on 26 December 2018, a M L 4.8 earthquake occurred near Pisano, destroying buildings and roads in two villages. We propose a time‐dependent intrusion model that supports the hypothesis of the inflation inducing flank deformation and that this process has been active since September 2018. Key Points: We show a model of the inflation phase preceding the 2018 eruption A time‐space evolution analysis, based on seismic and geodetic data, of the intrusive process of 24–25 December 2018 at Mount Etna is also proposed We also show a model of the posteruptive phase and its meaning for the evaluation of future volcanic hazards at Mt. Etna